Rehabilitation of the South American genus Sphenostigma Baker (Iridaceae: Tigridieae) - Deble, Leonardo Paz (Balduinia, 2026)
Sphenostigma is rehabilitated from the synonymy of Gelasine Herbert based on distinctive characteristics of the perigonium and mainly by shape of the gynoecium, which has a wide stigmatic area perpendicular to the style branches. Six species and four subspecies are recognized, six of them constitute new combinations: Sphenostigma Sellowianum (Klatt) Baker (type of the genus), S. caeruleum Klatt, S. giganteum (Ravenna) Deble subsp. giganteum, S. giganteum subsp. flexitepalum (Ravenna) Deble, S. paranaense (Ravenna) Deble, S. rigidum (Ravenna) Deble, S. uruguaiense (Ravenna) Deble subsp. uruguaiense, and S. uruguaiense subsp. orientale (Ravenna) Deble. Lectotypes are designated for Sphenostigma Sellowianum, S. giganteum subsp. flexitepalum and S. rigidum. A neotype is proposed for S. uruguaiense subsp. orientale. A list of valid names and synonyms is provided.